Students' attitudes to tick risks - Nejezchlebova, Helena; Kiewra, Dorota; Žákovská, Alena; Ovesná, Petra (AAEM. Annals of Agricultural and Environmental Medicine, 2016)
INTRODUCTION AND OBJECTIVES: The ever-increasing number of patients with tick-borne diseases resulted in the presented study investigating the awareness, attitudes and knowledge among students about the threats arising from tick bites and preventive anti-tick practices. MATERIALS AND METHOD: Questionnaires concerning these issues were distributed amongst Czech and Polish university students of science. Responses were analyzed by nationality and by gender. RESULTS: Nearly all respondents were aware of the risks arising from ticks and could name at least one disease transmitted by ticks. The Czech students felt more threatened by tick-borne diseases, had more frequently suffered from Lyme borreliosis and were vaccinated against tick-borne encephalitis more often than the Polish students. A large number of the participants applied preventive measures against ticks in order to protect themselves. The Czech students believed in the effectiveness of repellents statistically more often than the Polish students, while effectiveness is the main criterion for selection of the right repellent in both groups. CONCLUSION: Differences in preferences between the two nations appeared in many areas, e.g. the Czechs felt more threatened by all kind of risks and suffered from Lyme disease more frequently. Gaps can still be found in both the knowledge and behaviour among the respondents. It can be expected that the general public knowledge of this issue is rather limited in comparison with the students participating in the study, who are systematically educated in the field.
Keywords: kontrola klíšťat; Ticks; mužské pohlaví; Students; Male; Czech Republic; Tick Control; klíšťata; Female; Humans; Health Knowledge, Attitudes, Practice; lidé; Risk Assessment; ženské pohlaví; Poland; kousnutí klíštětem; Česká republika; mladiství; studenti; Tick Bites; Young Adult; Animals; Adolescent; zdraví - znalosti, postoje, praxe; zvířata; nemoci přenášené klíšťaty; Polsko; mladý dospělý; dospělí; Adult; Tick-Borne Diseases; hodnocení rizik